2020
DOI: 10.1002/mp.14579
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic organ motion and dosimetric implications during horizontal patient rotation for prostate radiation therapy

Abstract: Purpose Gantry‐free radiation therapy systems utilizing patient rotation would be simpler and more cost effective than the conventional gantry‐based systems. Such a system could enable the expansion of radiation therapy to meet global demand and reduce capital costs. Recent advances in adaptive radiation therapy could potentially be applied to correct for gravitational deformation during horizontal patient rotation. This study aims to quantify the pelvic organ motion and the dosimetric implications of horizont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…After maintaining the consistency of bladder volume, the centroid of the bladder was also compared in this study with the purpose to represent the position changes of the bladder. So far, the comparison of bladder centroids has been proposed in studies for uterine malignancy, 33 prostate cancer, 34 and bladder cancer 35 radiotherapy. Based on the results monitored by the Clarity system, it was found that the bladder displacement is clearly insignificant in most patients (see Table 3), providing the first evidence that the dual-guidance showed the therapeutic potential for postoperative uterine malignancy patients.…”
Section: Discussionmentioning
confidence: 99%
“…After maintaining the consistency of bladder volume, the centroid of the bladder was also compared in this study with the purpose to represent the position changes of the bladder. So far, the comparison of bladder centroids has been proposed in studies for uterine malignancy, 33 prostate cancer, 34 and bladder cancer 35 radiotherapy. Based on the results monitored by the Clarity system, it was found that the bladder displacement is clearly insignificant in most patients (see Table 3), providing the first evidence that the dual-guidance showed the therapeutic potential for postoperative uterine malignancy patients.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown in a proof-of that improving the accuracy of CBCT images will improve the accuracy of radiation therapy treatment. The level of treatment plan adaptation required to compensate for observed patient and target motion will be evaluated and the dosimetric impacts of no adaptation versus iso-centre shift and full plan re-optimisation will be compared in a similar fashion to Buckley et al [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Combination of neoadjuvant chemotherapy with radiotherapy is an optional treatment for patients with locally advanced sigmoid colon cancer (2), and it usually accompanies complete mesocolic excision (3,4). Considerable variation in the small intestine and bladder following pelvic and lower abdomen irradiation can lead to normal organ toxicity (5)(6)(7). Consequently, the goal of treatment is to improve the prognosis of patients, reduce toxicity and enable patients to complete treatment without interruption.…”
Section: Introductionmentioning
confidence: 99%